Surface-coupled proton exchange of a membrane-bound proton acceptor - Sandén, Tor (National Academy of Sciences, 2010)
Proton-transfer reactions across and at the surface of biological membranes are central for maintaining the transmembrane proton electrochemical gradients involved in cellular energy conversion. In this study, fluorescence correlation spectroscopy was used to measure the local protonation and deprotonation rates of single pH-sensitive fluorophores conjugated to liposome membranes, and the dependence of these rates on lipid composition and ion concentration. Measurements of proton exchange rates over a wide proton concentration range, using two different pH-sensitive fluorophores with different pK(a)s, revealed two distinct proton exchange regimes. At high pH (> 8), proton association increases rapidly with increasing proton concentrations, presumably because the whole membrane acts as a proton-collecting antenna for the fluorophore. In contrast, at low pH (< 7), the increase in the proton association rate is slower and comparable to that of direct protonation of the fluorophore from the bulk solution. In the latter case, the proton exchange rates of the two fluorophores are indistinguishable, indicating that their protonation rates are determined by the local membrane environment. Measurements on membranes of different surface charge and at different ion concentrations made it possible to determine surface potentials, as well as the distance between the surface and the fluorophore. The results from this study define the conditions under which biological membranes can act as proton-collecting antennae and provide fundamental information on the relation between the membrane surface charge density and the local proton exchange kinetics.